Tomoelastography for non-invasive detection of ameloblastoma and metastatic neck lymph nodes - Beier, Marie; Sack, Ingolf; Beck-Broichsitter, Benedicta; Hamm, Bernd; Marticorena Garcia, Stephan Rodrigo (BMJ Case Reports, 2020)
Ameloblastoma is a benign epithelial tumour and the most common odontogenic tumour, accounting for about 18% of cases. We present a patient to illustrate the first use of tomoelastography for quantitatively mapping tissue stiffness (shear wave speed) and fluidity (loss angle of the complex shear modulus) in a metastasised ameloblastoma of the left mandible. Tomoelastography maps clearly depicted the extent of the tumour by abnormally high values of stiffness and fluidity (1.73±0.23 m/s, 1.18±0.08 rad) compared with normal values in the contralateral mandible (1.04±0.09 m/s, 0.93±0.12 rad). Abnormal stiffness also revealed metastatic involvement of the neck lymph nodes (1.30±0.03 m/s vs 0.86±0.01 m/s). Taken together, stiffness and fluidity measured by tomoelastography can sensitively detect the presence and extent of bone tumours and metastatic spread to cervical lymph nodes.
CRIS-Team Scopus Importer:2022-08-03
Keywords: head and neck cancer; radiology; screening (oncology)